The Mediating Role of Basic Psychological Needs Satisfaction in the Relationship Between Metacognitive Beliefs and Learning Motivation in Adolescents - Taravian, Sara; Taghvaei Nia, Ali (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study aimed to investigate the mediating role of basic psychological needs satisfaction in the relationship between metacognitive beliefs and learning motivation among adolescents.Methods and Materials: This study employed a descriptive-correlational design using Structural Equation Modeling (SEM). The statistical population consisted of all high school students in Shiraz during the 2025–2026 academic year. A total of 321 students were selected through multi-stage cluster random sampling. Data were collected using the Metacognitive Beliefs Questionnaire, the Basic Psychological Needs Satisfaction Scale, and the Learning Motivation Questionnaire. Descriptive statistics, Pearson correlation coefficients, path analysis, Maximum Likelihood estimation, and bootstrapping with 5,000 samples were conducted using SPSS-26 and AMOS-24 software. The proposed model examined the direct and indirect relationships among positive and negative metacognitive beliefs, autonomy, competence, relatedness, and learning motivation.Findings: The findings indicated that the proposed model demonstrated an acceptable fit with the data. Negative metacognitive beliefs had significant negative effects on autonomy, competence, and relatedness, whereas positive metacognitive beliefs significantly predicted autonomy and relatedness. Autonomy and relatedness significantly predicted learning motivation, but competence did not show a significant direct effect on motivation. Bootstrapping analyses revealed that autonomy and relatedness significantly mediated the relationship between negative metacognitive beliefs and learning motivation. Specifically, increases in negative metacognitive beliefs were associated with lower autonomy and relatedness, which subsequently reduced learning motivation. However, competence did not mediate the relationship between negative metacognitive beliefs and learning motivation. Furthermore, none of the indirect paths associated with positive metacognitive beliefs were statistically significant.Conclusion: The findings suggest that maladaptive metacognitive beliefs undermine adolescents’ learning motivation primarily through the frustration of autonomy and relatedness needs.